PENDEKATAN NIRKEKERASAN DALAM MANAJEMEN KONFLIK PESANTREN MENURUT TAFSIR FAKHRUDDIN AR-RAZI - Albab Shodikin; Na'imah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Explores the application of nonviolence in conflict management within pesantren (Islamic boarding schools), based on the interpretation (tafsir) of Fakhruddin ar-Razi, a classical Islamic scholar known for his rational and philosophical exegesis. Conflicts in pesantren may arise due to differences in opinion, leadership styles, orimbalances in interpersonal relationships. The nonviolence approach offers apeaceful, dialogical, and just method of conflict resolution, in line with Islamic values.Ar-Razi’s tafsir, particularly his interpretation of verses related to peace, justice, andhuman interaction such as Surah Al-Hujurat (49): 9–10 and Surah An-Nahl (16): 125emphasizes persuasion, wisdom-based dialogue, and the prohibition of coercionand violence. These principles align with contemporary conflict resolution theoriesand present a valuable framework for managing disputes in pesantren environmentsconstructively and ethically. This research adopts a qualitative method with a libraryresearch approach, analyzing Ar-Razi’s tafsir works alongside contemporaryliterature on conflict management in Islamic educational settings. The study aims todevelop a contextual and applicable model of conflict resolution rooted in classicalIslamic thought and the ethos of nonviolence. By integrating ar-Razi’s interpretativeinsights with modern needs, pesantren can foster a culture of peace, dialogue, andmutual respect, contributing to the sustainability of Islamic education in plural anddynamic societies.